Knowledge, attitudes and practices of healthcare workers related to breastfeeding in the Motheo District, Free State - Hennop, Imke (University of the Free State, 2020)
Breastfeeding is widely recognised as the ideal method of infant feeding. Despite this, the percentage of South African mothers that breastfeed (especially exclusively for the first six months of life) remains alarmingly low. Healthcare workers (HCWs) play a key role in promoting, protecting and supporting breastfeeding. A lack of knowledge, negative attitudes and unfavourable practices of HCWs have a major impact on the protection, promotion and support of breastfeeding. Evidence-based recommendations for infants are continuously summarised by a number of organisations including the World Health Organization (WHO) and the United Nations Children’s Fund (UNICEF). The current study aimed to assess the breastfeeding knowledge, attitudes and practices (KAP) of HCWs whose responsibilities include supporting breastfeeding in the Motheo district, Free State. These findings were compared to the 2016 WHO and UNICEF guidelines on Infant and Young Child Feeding (IYCF) and 2018 Mother-Baby Friendly Initiative (MBFI) guidelines. A cross-sectional study design was applied in a total population of 117 HCWs, including paediatricians, obstetricians, general practitioners (GPs) and midwives working in the private and public healthcare sectors. Participants were registered with the Health Professions Council of South Africa (HPCSA) and South African Nursing Council (SANC). A self-developed questionnaire was used to obtain information related to sociodemographics (age, years practicing in current position, current place of employment and gender) and KAP related to breastfeeding. The questionnaire was selfadministered and available in paper and online format. The median age of participants was 34.0 years and the median years practicing in current profession was 7.0 years. The majority of GPs (85.9%) and midwives (82.1%) worked in public hospitals, while the majority of paediatricians (60%) and half of the obstetricians (50%) were in private practice. More than half of the participants were female (65.8%). In terms of knowledge related to breastfeeding, a significantly higher percentage of GPs (60.6%) than paediatricians (30%), obstetricians (25%), and midwives (50%) were able to list three benefits of breastfeeding for the baby (p=0.0180). Although the percentage of HCWs that could list three benefits of breastfeeding for the mother was low (26.7%), a higher percentage of GPs (33.8%) than paediatricians (20%), obstetricians (25%), and midwives (10.7%) were able to list three benefits of breastfeeding for the mother (p=0.0016). Almost ninety percent of HCWs (89.7%) knew that formula milk does not have the same nutrient composition as breast milk. Although the majority of the total group of HCWs (70%) knew that a breastfeed should not be time limited, a significantly higher percentage of obstetricians (100%) and midwives (82.1%) were aware of this compared to 40% of paediatricians and 66.2% of GPs (p=0.0015). Most HCWs (92.3%) knew that placing a baby in skinto-skin contact can contribute to the stabilisation of newborn blood glucose levels. Less than fifteen percent of the total group of HCWs (14.5%) were able to name at least one step of the MBFI 10 Steps to Successful Breastfeeding. In terms of knowledge pertaining to breastfeeding in the context of human immunodeficiency (HIV), only 6% of the total group of HCWs knew that breastfeeding is recommended for an HIV infected mother if the mother is from a lower socioeconomic background and does not meet the AFASS (Acceptable, Feasible, Affordable, Sustainable and Safe) criteria. Less than fifty percent (46.1%) of the total group of HCWs were aware of the newest 2017 WHO guideline pertaining to HIV and continued breastfeeding up to two years and beyond while being fully supported for antiretroviral therapy (ART) adherence. The majority of GPs (76.1%) and midwives (78.6%) recommend exclusive breastfeeding up to the age 6 months, compared to only 10% of paediatricians and 25% of obstetricians, who recommend exclusive breastfeeding for 4 - 6 months. Fewer than 30% of the total group of HCWs (28.3%) recommended continued breastfeeding together with complementary feeding up to 24 months and beyond.Half of the obstetricians and more than half of paediatricians (60%) en courage mothers to initiate breastfeeding within one hour after birth, compared to the majority of GPs (64.8%) and midwives (71.4%) who encourage mothers to initiate breastfeeding within half an hour after birth, a difference that was statistically significant (p=0.0137). If a mother and baby are separated after birth due to an inadvertent situation and the mother is still able to express enough breast milk, 60% of paediatricians and 50% of obstetricians would recommend using formula milk with a cup, compared to 80.3% GPs and 89.3% midwives who recommend breastmilk with a cup as feeding method (p<0001). Less than half the paediatricians (40%) and obstetricians (37.5%) recommended rooming in for 24 hours a day, compared to the majority of GPs (80.3%) and midwives (78.6%) (p=0.0152). If a baby did not regain birth weight before 2 weeks of age and the medical examination results are normal, 60% of paediatricians would recommend supplementing with formula, the majority obstetricians (100%), GPs (60.6%) and midwives (78.6%) would recommend the mother to breastfeed more often and only a quarter of HCW (15.4%) would refer the mother to a lactation specialist (p=0.0096).In terms of attitude toward breastfeeding, a significantly higher percentage of midwives than other HCWs felt highly confident to successfully show a new mother how to correctly position and attach the baby to the breast for breastfeeding a nd to give her breastfeeding advice (p=0.0004 and p=0.0050 respectively). Fewer than half of paediatricians (41%), GPs (40.8%) and 50% of midwives felt highly confident to give mothers advice on how to treat breastfeeding complications e.g. mastitis, bleeding nipples, breast abscess, engorgement, nipple bleb and blocked duct. Fifty percent of paediatricians and 37.5% of obstetricians believed that there is no harm in using pacifiers and/or bottles, compared to the majority of 71.8% GPs and 85.7% midwives who would not recommend the use of bottles and pacifiers, a difference that was statistically significant (p=0.0007). In terms of practices related to breastfeeding, more than half of the total group of HCWs (56%) had not previously completed the 20 hour WHO Lactation Management Training. Seventy percent of the paediatricians, 100% obstetricians and 56.3% GPs felt that the breastfeeding training that they received during their studies was not adequate and did not equip them to support and educate breastfeeding mothers, compared to more than half of midwives (57.1%) that felt that their breastfeeding training was adequate (p=0.0481).In conclusion, in-depth knowledge pertaining to certain important aspects of breastfeeding were lacking in all HCWs. In addition, a large percentage of HCWs were not confident to support mothers to breastfeed and their practices did not comply with the 2016 WHO Infant and Young Child Feeding guidelines and with the 2018 MBFI 10 Steps to Successful Breastfeeding. In order to successfully promote, protect and support breastfeeding, the 20 hour WHO Lactation Management Training should be implemented universally and regularly to ensure that HCWs stay updated with the most recent IYCF guidelines and MBFI 10 Steps to Successful Breastfeeding.
Dissertation (M.Sc. (Dietetics))--University of the Free State, 2020
Keywords: Breastfeeding - Health promotion; Health care professionals; Child growth; Breastfeeding promotion